DECENTRALIZED FINANCE (DEFI): OPPORTUNITIES AND RISKS IN THE FUTURE OF FINANCIAL ECOSYSTEMS - Zebua, Estera Asriani; Octafian, Ray (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Decentralized Finance (DeFi) has emerged as a significant innovation in the global financial ecosystem, offering an alternative for individuals who do not have access to traditional banking services. However, challenges such as regulatory uncertainty, security risks, and volatility of crypto assets hinder the widespread adoption of DeFi. This research aims to analyze the opportunities and challenges facing DeFi in the global financial system and evaluate its impact on financial stability and regulation. Using a Systematic Literature Review (SLR) approach, this research collects and analyzes literature from leading academic databases, including Scopus and Web of Science, with a focus on relevant studies between 2019 and 2024. Thematic and comparative analysis is applied to identify key themes and compare DeFi with traditional financial systems. The findings show that DeFi offers greater cost efficiency and accessibility, but also faces significant risks regarding volatility and security. Regulatory uncertainty in various countries is a barrier to wider adoption. This research provides important insights for regulators and industry players into how DeFi can serve as a complement to traditional financial systems, while emphasizing the need for a clear regulatory framework to support innovation and protect users.